A redox‐mediator‐doped gel polymer electrolyte applied in quasi‐solid‐state supercapacitors. Issue 2 (9th August 2013) - Yu, Fuda; Huang, Miaoliang; Wu, Jihuai; Qiu, Zhaoyuan; Fan, Leqing; Lin, Jianming; Lin, Yibing
ABSTRACT Methylene blue (MB) redox mediator was introduced into polyvinyl alcohol/polyvinyl pyrrolidone (PVA/PVP) blend host to prepare a gel polymer electrolyte (PVA‐PVP‐H2SO4‐MB) for a quasi‐solid‐state supercapacitor. The electrochemical properties of the supercapacitor with the prepared gel polymer electrolyte were evaluated by cyclic voltammetry, galvanostatic charge–discharge, electrochemical impedance spectroscopy, and self‐discharge measurements. With the addition of MB mediator, the ionic conductivity of gel polymer electrolyte increased by 56% up to 36.3 mS·cm−1, and the series resistance reduced, because of the more efficient ionic conduction and higher charge transfer rate, respectively. The electrode specific capacitance of the supercapacitor with PVA‐PVP‐H2SO4‐MB electrolyte is 328 F·g−1, increasing by 164% compared to that of MB‐undoped system at the same current density of 1 A·g−1. Meanwhile, the energy density of the supercapacitor increases from 3.2 to 10.3 Wh·kg−1. The quasi‐solid‐state supercapacitor showed excellent cyclability over 2000 charge/discharge cycles. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 39784.